Role of Armed Police Force, Nepal to Protect and Promotion of Human Rights - Timilsena, Surya Prasad (Journal of APF Command and Staff College, 2021)
The present article reveals the role and policy of Armed Police Force Nepal in safeguarding human rights. One of the primary missions of the APF Nepal is to protect the citizens from criminal activity and criminal elements and to maintain public order. This duty includes protecting the rights of every citizen. Armed forces have the duty to protect the individual human rights of every person they encounter. This is an affirmative duty, meaning the police services cannot knowingly ignore or intentionally fail to act when a human rights violation is observed. The Armed Police Force has mandated tasks related to protection, promotion, respect and fulfillment of human rights from various aspects. The research has reached in conclusion: Human rights are moral principles or norms that describe certain standards of human behavior and are regularly protected as a legal right in municipal and international law. They are commonly understood as inalienable, universal and indivisible fundamental rights to which a person is inherently entitled simply because she or he is a human being. To achieve this objective APF Nepal has adopted zero tolerance in Human Rights violations and following national and international human rights instrument that have been adopted by Nepal.